The efficacy of botanical pesticides in controlling coffee berry borer, Hypothenemus hampei (Ferrari, 1867) (Coleoptera: Curculionidae): A meta-analysis - Khodijah, Siti; Anggraini, Renny Tri; Andrianto, Eko; Lestari, Puji; Afandi, Auliana (Universitas Lampung, 2024)
Coffee berry borer pest (CBB) is one of the main pests that has a significant impact on coffee production and quality. In Indonesia, the utilization of plant-based pesticides has promising prospects in controlling CBB. The purpose of this study is to provide information on the impact of different types of plant pesticide on CBB mortality through a measurable algorithm analysis. A literature search was performed using Scopus, Web of Science, Google Scholar, Researchgate, and ScienceDirect. A linear mixed model (LMM) was applied to evaluate the effect of botanical pesticide application on the mortality rate of CBB. A total of 14 plant families were included in meta-regression analysis for estimating the effect size of each family. The average effect of pesticide exposure to CBB analyzed using LMM was 0.039 which mean that botanical pesticidal exposure has significant effect on the mortality rate of CBB (P<0.05). The results of this study suggested that the use of botanical insecticide especially derived from plants belonging to Family Anacardiaceae was significantly effective in controlling CBB.